Network Objects - Birrell, Andrew; Nelson, Greg; Owicki, Susan; Wobber, Ted (Proceedings of the 14th ACM Symposium on Operating System Principles, 1993)
A network object is an object whose methods can be invoked over a network. This paper describes the design, implementation, and early experience with a network objects system for Modula-3. The system is novel for its overall simplicity. The paper includes a thorough description of realistic marshaling algorithms for network objects.